Developing a Multidisciplinary Team for Disorders of Sex Development: Planning, Implementation, and Operation Tools for Care Providers - Mary Elizabeth Moran; Katrina Karkazis (Advances in Urology)
In the treatment of patients with disorders of sex development (DSD), multidisciplinary teams (MDTs) represent a new standard of care. While DSDs are too complex for care to be delivered effectively without specialized team management, these conditions are often considered to be too rare for their medical management to be a hospital priority. Many specialists involved in DSD care want to create a clinic or team, but there is no available guidance that bridges the gap between a group of like-minded DSD providers who want to improve care and the formation of a functional MDT. This is an important dilemma, and one with serious implications for the future of DSD care. If a network of multidisciplinary DSD teams is to be a reality, those directly involved in DSD care must be given the necessary program planning and team implementation tools. This paper offers a protocol and set of tools to meet this need. We present a 6-step process to team formation, and a sample set of tools that can be used to guide, develop, and evaluate a team throughout the course of its operation.